Working capital management - Preve, Lorenzo A.; Sarria-Allende, Virginia (New York ; Oxford : Oxford University Press, 2010)
This is a hands-on look at the crucial decision of how to define and finance the operating investments of a business. Starting with an overview of the fundamental framework of corporate finance, the authors set out to define the central, and usually underestimated, role that working capital plays within this structure.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Working capital